Perspectives on textile cleanliness – detecting human sebum residues on worn clothing. Issue 23 (December 2019) - Krifa, Mourad; Rajaganesh, Shamini; Fahy, William
Human sebum is one of the major constituents of oily organic soils found in worn clothing. While there are methods to evaluate visible aspects of fabric cleanliness, such as stains, there is no objective method to detect skin oils transferred to the garment through contact with the human body. This research aims at establishing the feasibility of using ozone decay rates in the presence of soiled fabric samples as a metric for measuring the amount of sebum. Our central hypothesis is based on the fact that ozone is highly reactive with some of the primary compounds found in skin lipids originating from sebaceous gland secretions. Ozone decay experiments were conducted in the presence of fabric samples contaminated with known amounts of sebum and modeled using the exponential decay function. The results obtained exhibited a significant relationship between the soil add-on and the ozone decay rates. The presence of skin lipids on fabric accelerated ozone decay. It appears feasible based on our results to detect the presence of soils on garments and thus assess cleanliness using the variation of ozone decay rates.